A clinico-mycological spectrum of superficial mycoses of scalp in pediatric population: A clinico-mycological spectrum of superficial mycoses of scalp - Faiza Zeeshan, Fakhur Uddin, Bahram Khan, Talat Zehra, Sadaf Razzak, Zareen Irshad, Faiza Zeeshan, Fakhur Uddin, Bahram Khan, Talat Zehra, Sadaf Razzak, Zareen Irshad (Journal of Rawalpindi Medical College, 2020)
Objective: A clinico-mycological study was conducted to assess the profile of dermatophytes and non-dermatophytes in patients with superficial mycoses of scalp. Methods: This Descriptive cross sectional study was conducted at Department of Microbiology, Basic Medical Sciences Institute, in collaboration with Department of Dermatology, Jinnah Postgraduate Medical Centre, Karachi. The study was carried out from May 2019 to September 2019. A total of 114 children were enrolled in the study having a clinical diagnosis of superficial mycoses of scalp. The hair specimens and scales from the scalp were collected. The specimens were processed for wet mounts (KOH and CFW staining) and mycological culture. . Results: The most common clinical presentation was found to be dermatophytoses (28%). Non-dermatophytoses was seen in 16.1% cases, while 55.2% cases were culture negative. The most common isolated dermatophyte was Trichophyton violaceum (35.4%), while among non-dermatophyte molds, Aspergillus spp accounted for 45% of cases. Conclusion: The unambiguous diagnosis of scalp mycoses can be made by mycological culture and conventional techniques like KOH mounts and CFW staining. Keywords: Calcoflour white stain, Dermatophytes, KOH mount, Tinea capitis